Are free radicals involved in IspH catalysis? An EPR and crystallographic investigation - Wang, Weixue; Wang, Ke; Span, Ingrid; Jauch, Johann; Bacher, Adelbert; Groll, Michael; Oldfield, Eric (Journal of the American Chemical Society, 2012)
The [4Fe-4S] protein IspH in the methylerythritol phosphate isoprenoid biosynthesis pathway is an important anti-infective drug target, but its mechanism of action is still the subject of debate. Here, by using electron paramagnetic resonance (EPR) spectroscopy and 2H, 17O, and 57Fe isotopic labeling, we have characterized and assigned two key reaction intermediates in IspH catalysis. The results are consistent with the bioorganometallic mechanism proposed earlier, and the mechanism is proposed to have similarities to that of ferredoxin, thioredoxin reductase, in that one electron is transferred to the [4Fe-4S] 2+ cluster, which then performs a formal two-electron reduction of its substrate, generating an oxidized high potential iron-sulfur protein (HiPIP)-like intermediate. The two paramagnetic reaction intermediates observed correspond to the two intermediates proposed in the bioorganometallic mechanism: the early π-complex in which the substrate's 3-CH 2OH group has rotated away from the reduced iron-sulfur cluster, and the next, η 3-allyl complex formed after dehydroxylation. No free radical intermediates are observed, and the two paramagnetic intermediates observed do not fit in a Birch reduction-like or ferraoxetane mechanism. Additionally, we show by using EPR spectroscopy and X-ray crystallography that two substrate analogues (4 and 5) follow the same reaction mechanism. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2021-09-24